1963
DOI: 10.1029/jz068i006p01605
|View full text |Cite
|
Sign up to set email alerts
|

Exponential rigidity spectrums for solar-flare cosmic rays

Abstract: A study of solar proton spectrums in the range from a few Mev to a few bey reveals that at most times the number spectrums of these particles near the earth may be represented by an exponential rigidity spectrum of the form J = Joe-P/•'o Such a spectral representation also applies to a particles. The rigidity, P, is the momentum per unit charge. Intensity-time characteristics of the solar protons are examined, and it is significant that propagation changes Po and Jo but not the exponential nature of the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
2

Year Published

1966
1966
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(70 citation statements)
references
References 34 publications
(12 reference statements)
2
66
2
Order By: Relevance
“…This result is consistent with earlier studies (Freier and Webber 1963) which have shown that exponentials in rigidity provide abetter fit to the solar proton data than do power laws in kinetic energy. Therefore, we shall present new calculations of nuclear reaction yields only for the exponential spectrum of equation (10) and the Bessel function spectrum of equation (11).…”
Section: Abramovitz and Stegun 1966) The Parameters S And E C For Posupporting
confidence: 82%
“…This result is consistent with earlier studies (Freier and Webber 1963) which have shown that exponentials in rigidity provide abetter fit to the solar proton data than do power laws in kinetic energy. Therefore, we shall present new calculations of nuclear reaction yields only for the exponential spectrum of equation (10) and the Bessel function spectrum of equation (11).…”
Section: Abramovitz and Stegun 1966) The Parameters S And E C For Posupporting
confidence: 82%
“…These data are available online at the NOAA National Geophysical Data Center (http://spidr.ngdc.noaa.gov/ spidr/). An integrated proton flux can be described by an exponential rigidity relation (Freier and Webber, 1963), which is used to convert the GOES measurements to differential proton fluxes over the energy range of 1-500 MeV on a grid of 78 logarithmically spaced energies. The shape of the resulting spectrum is Maxwellian.…”
Section: Particle Ionization Ratesmentioning
confidence: 99%
“…1, were obtained from the World Wide Web server for the NOAA National Geophysical Data Center at www.ndgc.noaa.gov/stp/ stp.html. The GOES measurements were converted to differential proton flux for 600 keV-2000 MeV range assuming that the flux can be described by the exponential rigidity relation (Freier and Webber, 1963). Because of the high magnetic latitude of our calculation point (66.46 • N), virtually all protons are able to enter the atmosphere (see e.g.…”
Section: Modelling the October 1989 Solar Proton Eventmentioning
confidence: 99%